1998
DOI: 10.1111/j.1365-2338.1998.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of secondary‐poisoning studies with rodenticides

Abstract: Rodenticides can become a danger for predators and scavengers if they prey on dead or moribund rodents. One possibility for assessing the hazard potential is to conduct trials in which poisoned rodents are fed to predators. Over the years, numerous such studies have been carried out with a wide range of carnivorous mammals and birds. Since an internationally recognized standard method only recently came into existence, the studies differ in details of trial procedure. The most significant end point is the mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The active ingredient in the rodenticide bait used in all trials was coumatetralyl (375 mg kg − 1 ; trade name Racumin; Bayer Environmental Science, Waltham Cross, Herts, UK), a first-generation, multiple-dose rodenticide with a half-life of 55 days in rat liver (Parmar et al . 1987) and relatively low toxicity to birds (Joermann 1998;Burn, Carter & Shore 2002). This was important because red kites (a protected species and the subject of a reintroduction programme in the UK) were present.…”
Section:  mentioning
confidence: 99%
“…The active ingredient in the rodenticide bait used in all trials was coumatetralyl (375 mg kg − 1 ; trade name Racumin; Bayer Environmental Science, Waltham Cross, Herts, UK), a first-generation, multiple-dose rodenticide with a half-life of 55 days in rat liver (Parmar et al . 1987) and relatively low toxicity to birds (Joermann 1998;Burn, Carter & Shore 2002). This was important because red kites (a protected species and the subject of a reintroduction programme in the UK) were present.…”
Section:  mentioning
confidence: 99%
“…However, given the persistence of rodenticides in prey and the ability for nontarget species to accumulate toxic doses over an extended period of time, many species of birds may be at significant risk with respect to anticoagulant rodenticide use. In a review of nearly 50 secondary poisoning studies with rodenticides, Joermann [19] concluded that anticoagulant rodenticides are acutely toxic. In a seven-year survey of nontarget wildlife poisonings in New York State, USA, anticoagulant rodenticide (diphacinone, chlorophacinone, brodifacoum)-poisoned birds accounted for more than half of the wildlife fatalities [20].…”
Section: Anticoagulant Rodenticide Toxicity To Birdsmentioning
confidence: 99%
“…(1999). For data on secondary poisoning and design of such studies, see Joermann (1998) and OEPP/EPPO (1995). A case study is described by Joermann et al .…”
Section: Explanatory Notesmentioning
confidence: 99%